Pulmonary hyalinizing granuloma presenting with dysphagia: a rare presentation. (January 2017) - Khan, Fazal; Hamid, Arsalan; Fatima, Benish; Hashmi, Shiraz; Fatimi, Saulat
A 25-year-old man presented with a 2-month history of dysphagia and past history of pulmonary and intestinal tuberculosis. A barium swallow showed a point of constriction 42 mm above the gastroesophageal junction. Computed tomography revealed large opacities in bilateral lung fields, encroaching more on the esophagus. The lesion progressively compressed the esophagus as it moved inferiorly. A right posterolateral thoracotomy was performed for sub-anatomical resection of the mass. A biopsy revealed homogenous whirling hyalinized collagen fibers, highly suggestive of pulmonary hyalinizing granuloma, with no evidence of malignancy. Pulmonary hyalinizing granuloma should be considered in the differential diagnosis of longstanding dysphagia.